System management and compensatory parenting: educational involvement after maternal incarceration - Branigan, Amelia R. (Criminology, 2023)
Research has demonstrated that paternal incarceration is associated with lower levels of educational involvement among fathers and primary caregivers, but little is known regarding caregiver educational involvement when mothers have been incarcerated. In this study, we present the first analysis of variation in school- and home-based educational involvement by maternal incarceration history, pairing survey and interview data to connect macro-level group differences with micro-level narratives of mothers’ involvement in their children's education. Our survey data demonstrate that children of ever-incarcerated mothers experience increased school-based educational involvement by their primary caregivers, regardless of whether the caregiver is the mother herself. Our interview data point to compensatory parenting as a key motivating factor in educational involvement, wherein a caregiver endeavors to "make up for" the child's history of maternal incarceration. Findings add to the literature demonstrating maternal incarceration as a distinct experience from both paternal incarceration and material disadvantage alone, and they suggest the need to explore the role of schools as potential points of productive institutional involvement for mothers with an incarceration history.